Village Rise Movement: An Integrated Solution to Improve Family Economy and Educational Literacy in Underdeveloped Areas - Tewu, Denny; Bernadetha Nadeak; Muh. Zuhdy Hamzah; Napoleon Sinaga (PT Inovasi Pratama Internasional, 2025)
Sukamantri Village in Cariu District, East Bogor Regency, is one of the underdeveloped areas that faces fundamental problems in terms of family economy and educational literacy. Low household income and minimal access to learning resources and educational participation are the main obstacles in the process of building an independent and competitive community. Through this Community Service (PkM) activity, the service team designed the